PEDAGOGICAL CONDITIONS OF IMPROVING ADMINISTRATIVE DECISIONS OF THE EDUCATION MANAGER IN THE CONDITION OF MARKET RELATIONS - Murodov Nodirbek Oybek o‘g‘li (Journals Park Publishing, 2023)
The current state of education management system development is characterized by the search for a new philosophy of social management. This process is related to the changes in economic relations, social consciousness, human values and trends taking place in our country. As social and moral problems become more acute, society's need for a highly qualified leader in the educational system is increasing. In this regard, the problem of improving management activities of education managers is updated, the solution of which in practice allows to ensure the compatibility of management goals and achieved results. This research describes the actual issue mentioned above.
Keywords: Manager, technology, trend, management technology, information resources, pedagogical conditions, integration, market relations.